Estudo da inclinação do corpo mandibular em relação ao plano sagital mediano : relação com dos resultados do traçado predictivo em cirurgia ortognática - Morganti, Mário Alexandre (2016)
The aim of this study was to evaluate the mandibular body as a key reference area to 22 transfer the planned anteroposterior movement in predictive tracing to the surgical field, as 23 indicated by Puricelli, E. The angle of this area to the midsagittal plane could lead to 24 distortions in this process. A sample of 61 CBCT scans were evaluated in the OsiriX 25 software in 3D MPR. A hypothetical 10mm measure was inserted in the midsagittal plane and its projection on the mandibular vestibular cortical was measured on both sides. Frontal 27 and lateral cephalograms, and panoramic radiographs, were created from the same CBCT 28 scan. Cephalometric and panorametric measurements were used in multiple linear 29 regression models to determine if an individualization of the mandibular body angle could 30 be estimated. A mean of 12.47mm(+/-0.48mm) projection was observed. There was no 31 significant difference in sides. There was a significant difference (p<0.001, CI 95%) with a 32 mandibular base orientation to a Frankfurt plane orientation, with the latter being 0,49mm 33 greater. There was no significance in multiple linear regression models, except for age 34 (p<0.05) and gender (p<0.01), but not clinically relevant. In conclusion, in average of 25% 35 should be added to the predictive tracing anteroposterior measurement.